The Impact of Corporate Governance Characteristics on Corporate Financial Performance in Palestine: Does Board Gender Matter? - Ali H. I. Aljadba; Majidul Islam; Monther Eldaia (The Indonesian Journal of Accounting Research, 2026)
This study examines the influence of corporate governance (CG) characteristics on the corporate financial performance (CFP) of publicly listed non-financial firms on the Palestine Exchange (PEX) from 2013 to 2022. It investigates whether female directors, financial expertise, non-executive directors, CEO duality, board size, and audit committee (AC) size improve CFP in a politically and economically unstable environment such as that in Palestine. Agency Theory and Resource Dependence Theory (RDT) underlie the research framework. These relationships were estimated using panel data regression analysis. Data were manually collected from the companies' published annual reports. The results show that board financial expertise and AC size were positively correlated with CFP, while CEO duality and board gender diversity were negatively associated with CFP. These findings imply that greater separation between the CEO and the Chairman, and a greater presence of financial experts, strengthen CG practices and CPF. This study contributes to the existing literature on CG in emerging markets, particularly PEX, and offers practical implications for regulators and policymakers to improve board composition and, in turn, oversight. Furthermore, it calls for stronger CG reforms to improve the accountability, transparency, profitability, and values of firms listed on PEX.